Local and transnational networking among female immigrant entrepreneurs in peripheral rural contexts: Perspectives on Russians in Finnmark, Norway - Munkejord, Mai Camilla (European Urban and Regional Studies, 2015)
Publisher's version, source: http://doi.org/10.1177/0969776415587122 . Social networks are vital to the start-up and development of new businesses. In immigrant entrepreneurship research, the key role of co-ethnic networks has been particularly highlighted. However, there is a lack of knowledge about the networking practices of immigrants who start businesses in a rural context where co-ethnic communities do not exist. In order to address this gap, this article highlights the experiences of female Russian immigrant entrepreneurs living in Finnmark in northernmost Norway. Finnmark in fact represents a particularly interesting geographical context for such an empirical focus. The article considers how social, economic and cultural contexts configure network relationships and reveals the important role of the family, and in particular the male spouse, representing a network of resources that may alleviate migrant disadvantage through affective ties. Moreover, it shows that the family of the immigrant entrepreneurs may be located both locally in the new context of settlement and transnationally in the country of origin, and in addition may be of both co-ethnic and cross-ethnic character.